2019
DOI: 10.3892/ol.2019.10678
|View full text |Cite
|
Sign up to set email alerts
|

Cross‑disease analysis identified novel common genes for both lung adenocarcinoma and lung squamous cell carcinoma

Abstract: Lung squamous cell carcinoma (LSCC) exhibits a number of similarities with lung adenocarcinoma (LA) in terms of copy number alterations. However, compared with LA, the range of genetic alterations in LSCC is less understood. In the present study, a large-scale literature-based search of LA-associated genes and LSCC-associated genes was performed to identify the genetic basis in common with these two diseases. For each of the LA-associated genes, a mega-analysis was performed to test its expression variations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In this study, we attempted to use a system biology approach to identify the not-yet discovered connections between both diseases, including the data mining of disease-gene relation data, the analysis of molecular pathways, and a mega-analysis of existing expression datasets. The integrated analysis of multiple modalities of data has been proven to be an effective way for disease mechanism study (Liu et al, 2019;Zhang et al, 2019;Lian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we attempted to use a system biology approach to identify the not-yet discovered connections between both diseases, including the data mining of disease-gene relation data, the analysis of molecular pathways, and a mega-analysis of existing expression datasets. The integrated analysis of multiple modalities of data has been proven to be an effective way for disease mechanism study (Liu et al, 2019;Zhang et al, 2019;Lian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nucleus (6) and cytoplasm (8) are another two common sub-cellular locations for the proteins encoded by the genes with transcriptional regulations altered in lung cancers. EPAS1 is known to be a major transcriptional regulator associated with the diagnosis and prognosis of lung cancers (Wang et al, 2018;De Bastiani and Klamt, 2019;Zhang et al, 2019). This study detects that sixteen EPAS1-regulated genes demonstrated quantitatively altered transcriptional regulations in lung cancers.…”
Section: Biological Inferences Of the Detected Transcriptional Regulamentioning
confidence: 81%